Eugene England : A Mormon Liberal - Haglund, Kristine (Book collections on Project MUSE., 2021)
"Eugene England championed an optimistic Mormon faith open to liberalizing ideas from American culture. At the same time, he remained devoted to a conservative Mormonism that he saw as a vehicle for progress even as it narrowed the range of acceptable belief. Kristine L. Haglund views England's writing through the tensions produced by his often-opposed intellectual and spiritual commitments. Though labeled a liberal, England had a traditional Latter-day Saint background and always sought to address fundamental questions in Mormon terms. His intellectually adventurous essays sometimes put him at odds with Church authorities and fellow believers. But he also influenced a generation of thinkers and cofounded Dialogue, a Mormon academic and literary journal acclaimed for the broad range of its thought. A fascinating portrait of a Mormon intellectual and his times, Eugene England reveals a believing scholar who emerged from the lived experiences of his faith to engage with the changes roiling Mormonism in the twentieth century"--